Effect of different pretreatment methods on structural carbohydrates of kenaf fiber - Nurul Aishah, Mazlan; Kamaliah, Abdul Samad; Hafizuddin, Wan Yussof; Syed Mohd Saufi, Tuan Chik (IOP Publishing, 2020)
The application of pretreatment on lignocellulosic biomass is considered as a critical step to alter the recalcitrant structure of biomass especially in bioconversion process. Different pretreatment may result in different modification effects which is important to be rationally evaluated before adoption in order to achieve high yield of end products. Therefore, this study was done to evaluate the effect of different pretreatment methods on kenaf in terms of their chemical and physical properties. Kenaf was subjected to alkaline pretreatment using 4.42% sodium hydroxide operated at 100 °C for 1 hour and acid pretreatment using 0.1% nitric acid which was run at 60 °C for 12 hours. Through characterization study, higher structural carbohydrates were found in alkaline pretreated kenaf compared to acid pretreated kenaf with 73.4% and 70.3% respectively. The SEM, XRD and FTIR analysis showed the significant different of biomass structure before and after pretreatment. From this study, pretreatment process has been verified can improve the biomass compositions to be utilized for chemicals production by disrupt the structure and remove lignin which can be proven by the increasing in structural carbohydrates and decreasing in lignin yield from this characterization study.